Gallium Arsenide Thin Films Grown by MOCVD With Various Growth Conditions - I. Hamidah; N. Yuningsih; P. Arifin; M. Budiman; M. Barmawi (Indonesian Journal of Physics, 2004)
GaAs films were usually grown by metal organic chemical vapor deposition (MOCVD) using AsH3 and trimethyl-gallium (TMGa) as precursors. In this study, trisdimethylamino-arsenic (TDMAAs) and TMGa had been successfully used as As and Ga precursor, respectively. For these experiments, the growth temperature was allowed to range from 580 to 600 oC, the total reactor pressure was varied from 50 to 70 torr, and the flows of hydrogen and nitrogen were varied from 200 to 400 sccm. The TDMAAs/TMGa ratio was kept at 4.5. The structural and electrical properties were characterized using SEM method and standard van-der Pauw Hall measurement, respectively. The best growth condition occurred at growth temperature of 580 oC, reactor pressure of 50 torr, H2/N2 ratio of 1,and V/III ratio of 4.5. This film had grain size of 1.08 µm, growth rate of 0.94 µm/h, 395 cm2/Vs mobility, and hole concentration of 3.44 x 1015 cm-3